Epidemiology and future trend predictions of ischemic stroke based on the global burden of disease study 1990–2021 - Jiayu Liu; Aoxi Xu; Zhifeng Zhao; Bin Ren; Zhao Gao; Dandong Fang; Bo Hei; Junzhao Sun; Xiangyang Bao; Lin Ma; Xiaoque Zheng; Yuxin Wang; et al. (Communications Medicine)
Abstract Background Visualizing the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 and predicting future disease burdens at global, regional, and national levels can help health policymakers develop evidence-based ischemic stroke (IS) prevention and cure strategies. Methods We stratify epidemiological parameters by sex, age, the World Bank’s classification of economies, and sociodemographic index (SDI) levels. We use frontier analysis to assess whether the burden of ischemic stroke (IS) in each country aligns with its level of economic development. We apply the Autoregressive Integrated Moving Average (ARIMA) model and the Bayesian age-period-cohort (BAPC) model to predict the burden of IS over the next 15 years. Results Here we show that IS accounts for 69.9 million prevalent cases, 7.8 million incident cases, 3.6 million deaths, and 70.4 million DALYs in 2021. In men, the global DALY rate of IS increases up to age 90–94 years and then decreases; however, for women, the rate increases up to the oldest age group (≥95 years). Regionally, we find that the association between the SDI and the age-standardized DALY rate of IS starts relatively flat, with a small peak up to a sociodemographic index of about 0.7, and then declines rapidly. Factors contributing most to the DALY rates for IS are high systolic blood pressure, high LDL cholesterol, and air pollution. Conclusions The disease burden of IS in medium-high SDI countries is still high, which means we could not meet the Sustainable Development Goal targets by 2030. Countries should formulate prevention and control measures suitable for their national conditions based on risk factors.